Work, Gender, and Immiseration in South Africa and India - Naidu, Sirisha C.; Ossome, Lyn (Review of Radical Political Economics, 2018)
In this paper, we broaden Marx’s immiseration thesis to articulate social reproduction under capitalist growth. Specifically, we compare the female labor market in the context of the wage economy, the family-household, and the state, three institutions that influence the productionreproduction system. Our observations lead us to conclude that the neoliberal growth path has exacerbated inequities in the opportunities for female workers in both countries. Our findings affirm both the differentiation and homogenization of conditions of reproduction under capitalist exploitation.
Keywords: Immiseration; Neoliberalism; Labor; Gender; Reproduction